2019
DOI: 10.3892/ol.2019.10224
|View full text |Cite
|
Sign up to set email alerts
|

EGFR, but not COX‑2, protein in resected pancreatic ductal adenocarcinoma is associated with poor survival

Abstract: The effects of EGFR and COX-2 protein overexpression on clinical outcomes in pancreatic ductal adenocarcinoma (PDAC) patients remains unclear. Therefore, the aim of the present study was to evaluate the protein expression of epithelial growth factor receptor (EGFR) and cyclooxygenase-2 (COX-2) in tumor cells in surgically resected PDAC, in comparison with clinicopathological characteristics and clinical outcomes. Immunohistochemical staining of formalin-fixed paraffin-embedded tissue derived from surgically re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Previous studies that have investigated the prognostic significance of COX−2 in PDAC showed inconsistent results. A study by Fagman et al on 32 patients with PDAC showed that COX−2 expression was not independently associated with survival [ 19 ]. Meanwhile, several studies have reported that COX−2 expression was independently associated with a worse OS for PDAC patients [ 20 , 21 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies that have investigated the prognostic significance of COX−2 in PDAC showed inconsistent results. A study by Fagman et al on 32 patients with PDAC showed that COX−2 expression was not independently associated with survival [ 19 ]. Meanwhile, several studies have reported that COX−2 expression was independently associated with a worse OS for PDAC patients [ 20 , 21 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is important that we study these proteins, because their overexpression could potentially represent prognostic factors in cancers. Several studies have investigated the utility of COX−2 expression for predicting the patient survival in PDAC, with conflicting results [ 19 , 20 , 21 , 22 ]. A meta−analysis by Wang et al reported that the PDAC patients who expressed COX−2 had worse survival than those who did not [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…EGFR is a transmembrane protein closely related to multiple pathological processes such as the proliferation, invasion, and metastasis of pancreatic cancer cells. Clinical studies have shown that the overexpression of EGFR could shorten the average overall survival rate of patients after PDAC resection and can be used as an independent predictor [ 39 ]. Accumulating evidence demonstrated that MAPK signaling promotes pathogenesis and biochemical progress of tumor cells [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…EGFR is highly expressed in a variety of tumours, and is associated with tumour occurrence and development and poor prognosis [ 74 , 75 ]. It has been reported that EGFR overexpression can be detected in up to 90% of PC tumour tissues, and that overexpressed EGFR is closely involved in the progression of PC and the poor prognosis of PC patients [ 76 , 77 ]. It was also confirmed that EGFR is an effective target for PC prevention and treatment [ 78 ].…”
Section: Discussionmentioning
confidence: 99%